ANALISIS KESULITAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI GUGUS SLAMET RIYADI KECAMATAN ROWOSARI KABUPATEN KENDAL - Ajeng Wahyu Yulianingrum; Iin Purnamasari; Prasena Arisyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the implementation of learning based on the Independent Curriculum (Kurikulum Merdeka), the difficulties faced by teachers, the efforts to overcome these challenges, and the pattern of teacher difficulties in the Slamet Riyadi Cluster, Rowosari District. The research uses a descriptive qualitative approach with data collected through observation, interviews, questionnaires, and documentation. The findings reveal that teachers face several obstacles, including limited references, suboptimal time management, inadequate facilities, and lack of readiness. Efforts made by teachers include attending training through teacher working groups (KKG), utilizing surrounding resources, sharing the use of teaching equipment, and enhancing understanding through professional development activities. The study recommends that teachers improve their competencies through self-directed learning and training, and that schools provide stronger support in terms of infrastructure and resources.